Unveiling the complexity of non-oxidative coupling of methane: A simplified kinetics approach - Gebrekidan Gebreyohannes, Tsegay; Woo Lee, Sung; Ju Han, Seung; Tae Kim, Yong; Ki Kim, Seok (Chemical Engineering Journal, 2023)
This study presents the generation and optimization of a detailed mechanism for the non-oxidative coupling of methane (NOCM), consisting of 1,112 species and 106,877 gas-phase reactions using Reaction Mechanism Generator. A mechanism reduction, performed in the Ansys Workbench, focused on four target products and employed various reduction methods, yielding an optimal skeletal mechanism of 178 species and 9,695 gas-phase reactions. Methane conversion and species concentration were evaluated using Chemkin-pro software, accounting for six independent variables, with temperature and pressure exhibiting the most significant impact. We observed that the formation rate of light hydrocarbons is higher at the initial position of the reaction, whereas aromatic hydrocarbons form more readily as reactor length increases and temperatures rise. Therefore, tailored reactor size and reaction conditions could improve the yield of C2 products under NOCM conditions. Further, a smaller reactor size at high temperatures and low pressure may optimize the formation of light hydrocarbons. Through sensitivity analyses, we identified critical reactions for product formation and aromatic coke precursors, thereby providing insights into gas-phase non-oxidative methane conversion. Further optimization studies are needed to investigate parameter interactions, aiming for optimal conversion with higher yields of target species and minimal aromatic coke precursors. These findings can inform effective reactor design and optimization strategies.
Keywords: Aromatic coke; Mechanism reduction; Methane conversions; Non-oxidative; Non-oxidative coupling; Non-oxidative methane conversion; Oxidative coupling of methane; Reaction mechanism; Reaction mechanism generator; Reaction network; Aromatic coke; Mechanism reduction; Non-oxidative methane conversion; Reaction mechanism generator; Reaction network